2022
DOI: 10.1111/bjet.13192
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the SMART program on cognitive and academic skills: A systematic review and meta‐analysis

Abstract: Online interventions promoted to enhance cognitive ability hold great appeal for their potential positive impact in social, employment, and educational domains. Cognitive training programs have, thus far, not been shown to influence performance on tests of general cognitive aptitude. Strengthening Mental Abilities with Relational Training (SMART) is an online program that claims to raise intelligence quotient (IQ). This systematic review and meta-analysis evaluates the effect of SMART on indices of cognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…In a systematic review and meta-analysis of the SMART programme (see May et al, 2022) just published in the British Journal of Educational Technology, that included only studies with control groups, we found a moderate effect size for SMART (g = 0.57) on non-verbal IQ. While we remain cautiously optimistic about the merits and premise of the SMART programme, we called for larger, more rigorous randomised controlled trials to be conducted to more adequately assess the efficacy of the programme.…”
Section: An Online Programme Based On Rft Strengthening Mental Abilit...mentioning
confidence: 79%
See 2 more Smart Citations
“…In a systematic review and meta-analysis of the SMART programme (see May et al, 2022) just published in the British Journal of Educational Technology, that included only studies with control groups, we found a moderate effect size for SMART (g = 0.57) on non-verbal IQ. While we remain cautiously optimistic about the merits and premise of the SMART programme, we called for larger, more rigorous randomised controlled trials to be conducted to more adequately assess the efficacy of the programme.…”
Section: An Online Programme Based On Rft Strengthening Mental Abilit...mentioning
confidence: 79%
“…was established to enhance cognitive ability (Cassidy et al, 2016). It is a gamified programme, that trains the ability to relate stimuli, or in other words, domain general reasoning (May et al, 2022). Just a small subset of possible relational frames (Same/Opposite; More than/Less than) are trained using arbitrary nonsense syllables over a series of 55 stages of increasing difficulty in the programme.…”
Section: An Online Programme Based On Rft Strengthening Mental Abilit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this synthesis was to conduct a systematic review of the existing literature on student privacy in online, hybrid and technology‐enhanced courses using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) approach (May et al, 2021). The review aims to: summarize the current state of knowledge on student perceptions of privacy in online, hybrid and technology‐enhanced courses, identify students' perceptions of their privacy and/or threats to their privacy in online, hybrid and technology‐enhanced courses, including data collection, storage and dissemination practices as well as instructional practices, highlight the gaps in the existing research. …”
Section: Introductionmentioning
confidence: 99%
“…Relational models of language and cognition are receiving increased attention in both cognitive science and behavioral psychology. For example, cognitive researchers have shown that relational reasoning is central to fluid intelligence developmentally ( Crone et al, 2009 ); behavioral psychologists have found that training in relational reasoning can impact intelligence in normally developing ( May et al, 2022 ) and developmentally delayed populations ( Dixon et al, 2021 ). Artificial general intelligence (AGI) is similarly drawing together research traditions in their focus on relational reasoning ( Johansson, 2019 ).…”
Section: Introductionmentioning
confidence: 99%